A case of primary ovarian failure with Nijmegen Breakage a chromosomal instability syndrome. (27th January 2023) - Elif Boncukçuoğlu, Ayşe; Akçay, Seçkin; Üstay, Özlem
Abstract: Introduction: Nijmegen Breakage Syndrome (NBS) is a rare autosomal recessive chromosomal instability syndrome, characterized by dysmorphic facial features, intrauterine growth retardation and short stature, recurrent sinopulmonary infections, combined immune deficiency, radiosensitivity, increased risk for cancer, as well as premature ovarian failure. Nibrin gene mutation is responsible for the pathogenesis of the disease. The mechanism of gonadal failure in NBS is thought to be meiotic arrest in gametocytes. Clinical Case: A 23-year-old female was admitted to the Marmara University endocrinology outpatient clinic because of secondary amenorrhea. Her first menarche occurred spontaneously at the age of 13, but she has never bled again afterwards. In physical examination, blood pressure was 109/68 mmHg, pulse was 80/min, and temperature was 36°C. Her height was 163 cm, and weight was 67 kg, BMI: 25.6 kg/m2. Midfacial prominent appearance, micrognathia, microcephaly was observed. Breast was assessed for II stage in Tanner scale. Ferriman–Gallwey score was 5. Psychomotor development was natural, cognitive dysfunction was not observed. Her three siblings and aunt had a history of infertility, also her parents were third degree consanguineous. The patient stated that she had recurrent sinopulmonary infections and used several antibiotics since childhood. However, there was no hospitalization due to infection by now. Her two older sisters died due to cancer when they were 10 and 21 years old. The patient had primary ovarian insufficiency according to elevated serum gonadotropins concentration and low serum estradiol concentration (Table 1 ). The uterus was 50 mm in size, its contours were smooth, and the echo of myometrium was diffusely homogeneous. Bilateral ovaries were not observed in the suprapubic pelvic US examination. Karyotype analysis was performed that was found 46, XX. When considering her family history, facial dysmorphic appearance, and findings of primary ovarian failure, genetic analysis revealed NM_001024688.2 c.625C>T(p.Q209*) homozygous mutation. The patient was started on hormone replacement therapy (estrogen 2 mg once daily, dydrogesterone 10 mg once daily) after the diagnosis. Genetic counseling, immunodeficiency and malignancy screenings were performed. Interestingly, despite the history of recurrent infection, total Ig levels and vaccine responses were normal. Although no malignancy was observed in our case, it is noteworthy that two older sisters died due to cancer. It was recommended to continue the annual screenings. Table 1. The biochemical parameters of the patient. Conclusion: Family history should be thoroughly questioned in patients presenting with hypogonadism. NBS should be kept in mind as a rare cause in the presence of a typical phenotypic appearance, recurrent infections, and a family history of infertility and malignancy.